2018
DOI: 10.1590/2177-6709.23.4.036-042.oin
|View full text |Cite
|
Sign up to set email alerts
|

There is no pulp necrosis or calcific metamorphosis of pulp induced by orthodontic treatment: biological basis

Abstract: To biologically explain why the orthodontic treatment does not induce pulp necrosis and calcific metamorphosis of the pulp, this paper presents explanations based on pulp physiology, microscopy and pathology, and especially the cell and tissue phenomena that characterize the induced tooth movement. The final reflections are as follows: 1) the orthodontic movement does not induce pulp necrosis or calcific metamorphosis of the pulp; 2) there is no literature or experimental and clinical models to demonstrate or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Several studies have been focused on morphological and protein changes in the bone and periodontal ligament during orthodontic tooth movement [ 2 , 21 , 22 , 23 , 24 , 25 , 26 ]; recently, the literature has also been paying attention to dental pulp response to low force application.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have been focused on morphological and protein changes in the bone and periodontal ligament during orthodontic tooth movement [ 2 , 21 , 22 , 23 , 24 , 25 , 26 ]; recently, the literature has also been paying attention to dental pulp response to low force application.…”
Section: Resultsmentioning
confidence: 99%
“…This was demonstrated in a recent in vivo study involving human dental pulp where no irreversible iatrogenic changes were observed in the dental pulp following application of appropriate orthodontic forces for tooth movement (Vermiglio et al, 2020). Orthodontic tooth movement is not a direct cause of pulpal necrosis (Consolaro & Consolaro, 2018;Weissheimer et al, 2021) and obliteration of the dental pulp, but when these are observed following orthodontic tooth movement, a previous history of dental trauma could possibly be the aetiological factor (Javed et al, 2015;Yang et al, 2016;Consolaro & Consolaro, 2018). This might explain a higher frequency of pulpal necrosis in teeth with severe periodontal tissue injuries that underwent orthodontic treatment, mainly was attributable to the previous history of dental trauma ( Bauss et al, 2008;Bauss et al, 2010).…”
Section: Effects Of Orthodontic Treatment On Dental Pulpmentioning
confidence: 89%
“…One of the issues that raises the most questions and uncertainties in the orthodontic and endodontic clinical practice is the time at which a tooth may be moved after the completion of an endodontic procedure. This study extrapolates experimental and clinical knowledge accumulated from studies and clinical cases [1][2][3][4][5][6][7][8][9][10][11] , particularly as there are no specific data about it in the relevant literature.…”
Section: Orthodontic Insightmentioning
confidence: 97%